دراسة إحصائية لنقص فيتامين د عند النساء في مدينة اللاذقية - بيازيد, لطيفة جميل (Latakia University Journal -Medical Sciences Series, 2014)
الهدف من البحث معرفة نسبة نقص فيتامين د, ومعرفة أهم الأمراض المرافقة لنقصه. أجري هذا البحث في عيادة خاصة في مدينة اللاذقية بين العامين(2012-2013) تضمنت الدراسة127حالة من خلال عينة عشوائية, تمت الدراسة : وفقاً لنتائج فيتامين د مخبرياً : قيمة طبيعية - نقص معتدل- نقص شديد وفقاً لفئات العمر: مجموعة 1 : 20 - 50 سنة ، مجموعة 2 : أكثر من 50 سنة . تم التوصل إلى أن نسبة نقص فيتامين د مخبرياً عالية جداً بلغت 84,26% والنسبة الطبيعية 15,74%. نسبة النقص المعتدل لفيتامين د 55,15% . نسبة النقص الشديد44,85%. وفقاً لفئات العمر: المجموعة1: سيطرة الأعراض السريرية أكثر من الحالات المرضية. الأعراض السريرية:1- التعب العضلي93,70% ، 2-القلق والاكتئاب77,05%. الحالات المرضية:1-اضطرابات الدرق12,5% ، 2- ارتفاع التوتر الشرياني6,25% . المجموعة2: سيطرة الحالات المرضية . الأعراض السريرية:1- اضطرابات النوم والقلق 85,18% .2-التعب العضلي:74,07%. الحالات المرضية:1- أمراض القلب والأوعية 44,44%. 2- ارتفاع التوتر الشرياني37,03%. This study tries to know the rate of the deficiency of vitamin D experienced by Lattakian women as well as its accompanying diseases. It is conducted at a specific clinic in Lattakia in the period (2012-2013). The study included a sample of 127 women randomly chosen. It depended on laboratory results of the levels of vitamin D: normal rate, moderate deficiency, acute deficiency. It also depended on age group: Group1(20-50 years old): Group 2: (more than50 years old). The study concludes that the rate levels are as follows: very high (84.26%), normal (15.74%), moderate deficiency (55.15)%, and acute deficiency (44.85%). Symptoms based on age were as follows: Group 1: clinical symptoms were more visible than diseases. The clinical symptoms were: 1-the muscular vatic (93.70%); 2 anxiety and depression (77.05%). Diseases were: 1-thyroied failure (12.5%), 2-hypertesion(6.25%). Group 2: Diseases were more visible: The clinical symptoms were :1-anxiety (85.18%), 2-the muscular vatic (74.07%). Diseases were :1-cardiovasculardiseases (44.44%), 2-hypertension(37,03%).